PENGARUH HARGA QUEEN STAR WATERPARK TERHADAP KEPUASAN KONSUMEN - Yuni Rahayu; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Problems encountered with regard to customer satisfaction on Quuen Star Waterpark is the reduction in visits level over the last 3 years. pricing, is one factor that has been attempted by the company but have not been able to contribute a maximum of customer satisfaction . The purpose of this study was to determine the effect of pricing of customer satisfaction on Queen Star Waterpark.The research aims to analyze how the influence of price toward customer satisfaction. Sampling method uses Accidental Sampling Method. Sample of trhe research is 96 Queen star’s customer and then an analysis is performed toward the obtained data by using data analysis quantitatively and qualitatively. Quantitatively analysis includes: validity and realibility test, simple regression analysis and hypothesis test through t, and determination coefficient analysis (R). Qualitative analysis is an interpretation of the obtained data within research andthe result of data processing has been implemented by providing information andexplanation. Data has complied validity, realibility, so that those are resulting regression equation as follows:Y = 4,983+ 0,407 XWhere, Customer Satisfaction (Y), Price variable (X). Hyphothesis test uses t test demonstrates that the three of examined independent variables is proved significantly have a partially effect on dependent variable of Customer Satisfaction. The grade of R Square is 0,177 demonstrates that 17,7% percent of Customer Satisfaction variable can be explained by the three of independent variables within regression equation. While, the remainder is 82,3 percent is explained by other variables outside of those variable other used in the research.Keywords: Price, customer satisfaction